Implementation of Digital Marketing Strategies in MSMEs ÔÇ£KJ SepatuÔÇØ in Sumbersari Village Through Instagram Social Media - Anditasari, Putri (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2024)
This article discusses the implementation of digital marketing strategies for Micro, Small, and Medium Enterprises (MSMEs) in Sumbersari Village, Ciparay District, Bandung Regency. The background of this research is the limited knowledge and resources of MSMEs in utilizing digital technology for marketing. The purpose of this research is to identify and implement effective digital marketing strategies to increase the competitiveness of MSMEs, especially MSMEs "KJ Sepatu". The service method applied in this study is the┬áSisdamas method based on community empowerment, which is a work program that is carried out and refers to the condition of the community and the KKN-assisted area. The results of the study show that the implementation of digital marketing, such as the use of Instagram social media, can help MSMEs expand their market reach and increase sales. However, challenges such as lack of technological knowledge and infrastructure limitations still exist. The conclusion of this study emphasizes the importance of continuous education and assistance for MSMEs to optimize digital marketing strategies. The implication of this study is the need for collaboration between the government, communities, and the private sector to support the digital transformation of MSMEs in order to improve the local economy